Podcasting for dummies ebook - Morris, Tee (2020)
Add your voice to the podcasting revolution!  The world is tuning into podcasts in larger and larger numbers. When you're ready to add your own voice to the mix, this book will help you find your niche. Featuring top tech information, production insight, and promotional tips, this best-selling podcasting reference shares the latest on podcasting trends and new audience demographics.  Written by a pair of podcasting pioneers,  Podcasting For Dummies  will help you refine your podcast idea, identify your audience, and get the scoop on how to record, edit, and share your work. You'll also learn how to apply the methods top podcasters monetize and market their work.  Record your voice and conduct high-quality interviews for your new or existing podcast  Edit, upload, and share podcast episodes online—and find people who will listen  Learn how to make money as a podcaster or live streamer  Discover interesting and original podcasts to inspire your own work  Podcasting for Dummies  is your friendly tutor in the art of audio content creation. So start talking!